The Frequency of DPYD c.557A>G in the Dominican Population and Its Association with African Ancestry - Mariela Guevara; Carla González de la Cruz; Fernanda Rodrigues-Soares; Ernesto Rodríguez; Caíque Manóchio; Eva Peñas-Lledó; Pedro Dorado; Adrián LLerena (Pharmaceutics)
Background/Objectives: Genetic polymorphism of the dihydropyrimidine dehydrogenase gene (DPYD) is responsible for the variability found in the metabolism of fluoropyrimidines such as 5-fluorouracil (5-FU), capecitabine, or tegafur. The DPYD genotype is linked to variability in enzyme activity, 5-FU elimination, and toxicity. Approximately 10–40% of patients treated with fluoropyrimidines develop severe toxicity. The interethnic variability of DPYD gene variants in Afro-Latin Americans is poorly studied, thereby establishing a barrier to the implementation of personalized medicine in these populations. Therefore, the present study aims to analyze the frequency of DPYD variants with clinical relevance in the Dominican population and their association with genomic ancestry components. Methods: For this study, 196 healthy volunteers from the Dominican Republic were genotyped for DPYD variants by qPCR, and individual genomic ancestry analysis was performed in 178 individuals using 90 informative ancestry markers. Data from the 1000 Genomes project were also retrieved for comparison and increased statistical power. Results and Conclusions: The c.557A>G variant (decreased dihydropyrimidine dehydrogenase function) presented a frequency of 2.6% in the Dominican population. Moreover, the frequency of this variant is positively associated with African ancestry (r2 = 0.67, p = 1 × 10−7), which implies that individuals with high levels of African ancestry are more likely to present this variant. HapB3 is completely absent in Dominican, Mexican, Peruvian, Bangladeshi, and all East Asian and African populations, which probably makes its analysis dispensable in these populations. The implementation of pharmacogenetics in oncology, specifically DPYD, in populations of Afro-Latin American ancestry should include c.557A>G, to be able to carry out the safe and effective treatment of patients treated with fluoropyrimidines.